2019
DOI: 10.29390/cjrt-2018-016
|View full text |Cite
|
Sign up to set email alerts
|

Fluid management in Acute Respiratory Distress Syndrome: A narrative review

Abstract: Acute Respiratory Distress Syndrome remains a major source of morbidity and mortality in the modern intensive care unit (ICU). Major advances in the understanding and management of this condition were made in the last two decades. The use of low tidal ventilation is a well-established therapy. Conservative fluid management is now another cornerstone of management. However, much remains to be understood in this arena. Assessing volume status in these patients may be challenging and the tools available to do so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 101 publications
0
19
0
2
Order By: Relevance
“…2 In the absence of the need for restoration of depleted intravascular volume, the recommendation is to minimise fluids. 3 Interestingly, no patients received a fluid bolus in the authors' cohort of patients. It would be helpful if the authors had clarified the evidence base or experience to support use of a fluid bolus despite not having implemented the strategy themselves.…”
mentioning
confidence: 85%
“…2 In the absence of the need for restoration of depleted intravascular volume, the recommendation is to minimise fluids. 3 Interestingly, no patients received a fluid bolus in the authors' cohort of patients. It would be helpful if the authors had clarified the evidence base or experience to support use of a fluid bolus despite not having implemented the strategy themselves.…”
mentioning
confidence: 85%
“…Not surprisingly, a recent autopsy study in patients deceased from COVID-19 reported cardiomegaly with right ventricular dilatation, which could be a result of ARDS itself compounded by fluid overload and the effects of positive pressure ventilation [8]. Paradoxically, overzealous attempts at keeping such patients "dry" may not be an optimal strategy as reduction in cardiac output and pulmonary blood flow would lead to an increase in alveolar and physiological dead space, ultimately worsening the gas exchange [9]. Further complicating the picture, cytokine storm is a known feature of COVID-19, which can lead to increased vascular permeability, worsening pulmonary edema, third-space fluid loss, intra-abdominal hypertension, and multiorgan failure [10].…”
Section: Why Is Volume Status Assessment Complicated?mentioning
confidence: 99%
“…Fara aetti varlega með vökvagjöf í aeð þar sem SARS-CoV-2 getur skaðað hjartavöðvann auk þess sem leitast er við að halda neikvaeðu vökvajafnvaegi við meðferð á bráðu andnauðarheilkenni, ARDS (acute respiratory distress syndrome), sem er vel þekktur fylgikvilli COVID-19. 2,7,9 Þar sem prókalsítónín er almennt ekki haekkað í COVID-19 er einkum stuðst við það til að meta þörf á sýklalyfjum, en prókalsítónín er talið haekka sérstaklega í bakteríusýkingum. Samkvaemt meðferðarleiðbeiningum Landspítala ber að forðast notkun ytri öndunarvéla og háflaeðis súrefnisgjafar vegna haettu á að framkalla loftborið smit, sem veldur aukinni sýkingarhaettu fyrir starfsfólk og aðra sjúklinga.…”
Section: Inngangurunclassified